Drug‐naïve first‐episode schizophrenia spectrum disorders: Pharmacological treatment practices in inpatient units in Hunan Province, China. Issue 4 (14th September 2020) - Zhu, Mengran; Ferrara, Maria; Tan, Wenjian; Shang, Xingbo; Syed, Sumaiyah; Zhang, Li; Qin, Qilin; Hu, Xinran; Rohrbaugh, Robert; Srihari, Vinod H.; Liu, Zhening
Abstract: Aim: This study describes antipsychotic prescription patterns for drug‐naïve inpatients diagnosed with first‐episode schizophrenia‐spectrum (FES) disorders and factors associated with practices deviating from China's current guidelines. Methods: All inpatients aged 7 to 45 years experiencing a first episode of schizophrenia‐spectrum disorder with a duration of untreated illness of less than 18 months and admitted between 1 August 2016 and 1 August 2017 to one of eight psychiatric hospitals in Hunan were included. Demographics, clinical characteristics and prescriptions at discharge were collected from electronic medical records. Logistic regression and random forest methods were used to model relationships between demographic and clinical factors and deviations from China's guidelines. Results: Of the 602 inpatients included in the study, 598 (99.3%) were prescribed antipsychotics, and no patients were discharged on long‐acting injectable antipsychotics. Polypharmacy (more than one antipsychotic prescribed) was present in 121 (20.2%) participants. Clozapine was prescribed to 45 (7.5%) patients. Adults receiving polypharmacy were more likely to be prescribed high‐dose antipsychotics than those receiving a single antipsychotic. Minors under 13 years of age were more likely to receive polypharmacy and unapproved antipsychotics than those older than 13 years. Conclusions: Our findings suggest that most of the inpatients were prescribed a single antipsychotic at discharge, consistent with China's guidelines. Minors with FES and patients discharged on polypharmacy and clozapine may require more intense monitoring and management. With the current implementation of China's National Mental Health Working Plan, these results will assist decision‐makers in allocating resources and conducting reforms to facilitate best practice treatment for FES.